High-Resolution Fluorespirometry to Assess Dynamic Changes in Mitochondrial Membrane Potential in Human Immune Cells - Valencia, Ana P; Pharaoh, Gavin; Brandao, Arthur F; Marcinek, David J (Journal of visualized experiments, 2024)
Peripheral mononuclear cells (PBMCs) exhibit robust changes in mitochondrial respiratory capacity in response to health and disease. While these changes do not always reflect what occurs in other tissues, such as skeletal muscle, these cells are an accessible and valuable source of viable mitochondria from human subjects. PBMCs are exposed to systemic signals that impact their bioenergetic state. Thus, expanding our tools to interrogate mitochondrial metabolism in this population will elucidate mechanisms related to disease progression. Functional assays of mitochondria are often limited to using respiratory outputs following maximal substrate, inhibitor, and uncoupler concentrations to determine the full range of respiratory capacity, which may not be achievable in vivo. The conversion of adenosine diphosphate (ADP) to adenosine triphosphate (ATP) by ATP-synthase results in a decrease in mitochondrial membrane potential (mMP) and an increase in oxygen consumption. To provide a more integrated analysis of mitochondrial dynamics, this article describes the use of high-resolution fluorespirometry to measure the simultaneous response of oxygen consumption and mitochondrial membrane potential (mMP) to physiologically relevant concentrations of ADP. This technique uses tetramethylrhodamine methylester (TMRM) to measure mMP polarization in response to ADP titrations following maximal hyperpolarization with complex I and II substrates. This technique can be used to quantify how changes in health status, such as aging and metabolic disease, affect the sensitivity of mitochondrial response to energy demand in PBMCs, T-cells, and monocytes from human subjects.